Une architecture sensible au contexte pour le développement des systèmes d'administration pour l'enseignement - Bergeret, Gaël; Viana, Windson; Filho, José Bringel; Jose, Jr C F [UNESP]; Villanova-Oliver, Marlène; Gensel, Jérôme; Martin, Hervé (Association for Computing Machinery (ACM), 2009)
The increasing use of mobile devices and wireless communication technologies has improved the access to web information systems. However, the development of these systems imposes new challenges mainly due to the heterogeneity of mobile devices, the management of context information, and the complexity of adaptation process. Especially in this case, these systems should be runable on a great number of mobile devices models. In this article, we describe a context-aware architecture that provides solutions to the challenges presented above for the development of education administration systems. Copyright 2009 ACM.
Keywords: context-awareness; mobile computing; web applications; Adaptation process; Administration system; Context information; Context-Aware; WEB application; Web information systems; Wireless communication technology; Mobile computing; Mobile devices; Portable equipment; Wireless telecommunication systems; World Wide Web